2017
DOI: 10.4155/ipk-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Exogenous Biotin and the Relationship Between Biotin Serum Levels and In Vitro Immunoassay Interference

Abstract: Aim: Biotin in human serum is a potential interfering factor for streptavidin-biotin-based assays. We aimed to evaluate the effective half-life of biotin and biotin metabolites, and establish a pharmacokinetic (PK) model to simulate the time taken for the biotin concentration to fall below a series of thresholds. Materials & methods: PK properties of biotin (5, 10 and 20 mg daily) were evaluated in healthy participants. Biotin serum concentrations were simulated for high-dose regimens (1 mg daily to 300 mg q.i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 14 publications
0
55
0
Order By: Relevance
“…In the last decade, very high-doses of biotin (300 mg/day) have been shown to have a beneficial effect in patients suffering from progressive multiple sclerosis ( 4 ). Recently, interference removal protocols have been proposed to eliminate biotin in samples ( 5 , 6 ). Such protocols using pre-incubation with streptavidin-coated magnetic particles contained in Elecsys® immunoassay kits are easy to implement in laboratory workflow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, very high-doses of biotin (300 mg/day) have been shown to have a beneficial effect in patients suffering from progressive multiple sclerosis ( 4 ). Recently, interference removal protocols have been proposed to eliminate biotin in samples ( 5 , 6 ). Such protocols using pre-incubation with streptavidin-coated magnetic particles contained in Elecsys® immunoassay kits are easy to implement in laboratory workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Such protocols using pre-incubation with streptavidin-coated magnetic particles contained in Elecsys® immunoassay kits are easy to implement in laboratory workflow. Studies conducted so far recommend an incubation time of neutralization protocol from 45 minutes to 1 hour which can be a concern in terms of turnaround times for an emergency biomarker ( 5 , 6 ). At Rouen University Hospital, we perform approximately 50,000 hs-cTnT assays each year and up to 40% are for the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al studied biotin interference in vitro in various biotin‐based immunoassays on Vitros 5600 analyzer and observed that biotin at 6.25 ng/mL affected TSH assay causing more than 20% negative bias. Serum biotin level after taking 5 mg supplement/day varied from 10 to 73 ng/mL . Therefore, even taking 5 mg biotin, TSH measurement using Vitros 5600 analyzer may be affected.…”
Section: Discussionmentioning
confidence: 99%
“…In general, serum biotin levels in individuals taking no biotin supplement vary from 0.4 to 1.2 ng/mL . Grimsey et al studied serum biotin levels after volunteers consumed 5, 10, or 20 mg biotin and reported that serum biotin levels after taking 5 mg supplement/d varied from 10 to 73 ng/mL. However, after taking 20 mg biotin per day the observed serum biotin levels ranged from 80 to 355 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…It is rapidly absorbed with a serum half-life of 15 h and only reaches a steady state after 3 days. 21 Several other studies unravel a washout period up to 73 h for multiple sclerosis patients on 300 mg/day biotin doses. Therefore, there is insufficient evidence to support recommendations for safe testing in patients, taking high levels of biotin on a daily basis.…”
Section: Acs Omegamentioning
confidence: 99%